Unearthing the gap a critical discourse analysis of the mining reportage of community newspapers in the Cordillera Administrative Region - Del Rosario, Reynald Denver Z. 1998- (2018)
"The study described how community newspapers in the Cordillera Administrative Region (CAR) - namely, Amianan Balita Ngayon, Baguio Herald Express, Baguio Midland Courier and Northern Dispatch Weekly - reported on mining. Specifically, the study identified the emergent discourses in the mining reportage and looked into the socio-political and cultural factors affecting the discourses. Thomas Huckin's Critical Discourse Analysis, the Public Sphere Theory, and the Media Hegemony Theory were used as theoretical anchors for this study. Textual analysis was employed as a qualitative method for the study which operated on three levels: the socio-political and cultural context of the discourse, the individual articles, and the newspapers. The study identified four emergent discourses in the mining reportage - namely, adherence to law, the situation of mining communities, nation-building and economic development, and the anti-mining movement. Apparent in the dominant discourses are the ideological hegemony and power imbalances present in the context - the state and the mining firms were dominantly featured in the reportage, while the local communities and the anti-mining movement were sidelined."